Assessment of menopausal symptoms among women attending various outreach clinics in South Canara District of India - Joseph, Nitin (Medknow Publications & Media Pvt Ltd, 2014)
INTRODUCTION: Menopausal symptoms experienced by women are known to affect their quality-of-life. The symptoms experienced at menopause are quite variable and their etiology is found to be multifactorial. This study was hence done to assess the pattern and severity of menopausal symptoms and to find out the factors associated with these symptoms. MATERIALS AND METHODS: This cross-sectional study was conducted in various outreach clinics of Kasturba Medical College, Mangalore. Women in the age group of 40-65 years were included in the study by convenient sampling method. Data regarding menopausal symptom was obtained by interviewing each participant using the menopause rating scale questionnaire. RESULTS: Mean age of the participants were 54.2 ± 7.2 years and mean age of attainment of menopause was 48.4 ± 4.5 years. Mean duration of menopause was found to be 7.5 ± 5.3 years. Commonest symptom reported was joint and muscular discomfort and physical and mental exhaustion seen in 94 (85.4%) participants. The mean number of symptoms reported by participants was 7.6 ± 2.8. Educated women reported significantly more symptoms (F = 2.218, P = 0.047). Somatic and urogenital symptoms were more among perimenopausal women and somatic symptoms were more among postmenopausal women. Fifty-eight (52.7%) participants had one or more severe symptoms. Severe symptoms were most among premenopausal women. CONCLUSION: The high proportion and severity of menopausal symptoms observed in this study group proves that menopausal symptoms are common and cannot be ignored. More of menopausal clinics are needed for awareness generation, early recognition and treatment of related morbidities.